Anti-Developmental Effects of Imazosulfuron on Zebrafish Embryos During Development - Sunwoo Park; Gwonhwa Song; Whasun Lim (Journal of Animal Reproduction and Biotechnology, 2020)
Imazosulfuron is globally considered as a relatively safe herbicide that controls plant growth by interfering with amino acid synthesis. It is stable, persists in the soil, and has low toxicity; however, studies about the toxic effects of imazosulfuron on non-targeted aquatic vertebrates are scarce. In this study, imazosulfuron was able to induce acute lethality on zebrafish embryos within 48 h. Imazosulfuron also had adverse effects on heartbeats and induced abnormal development with pericardial edema and scoliosis. Moreover, apoptosis and oxidative stress were increased by imazosulfuron in a dose-dependent manner. Thus, all our results showed that imazosulfuron has toxic effects on zebrafish embryogenesis.